Dual inhibition of hepatic ACLY and ACSS2: A synergistic approach to combat NAFLD through lipogenesis reduction and mitochondrial enhancement - Mengdi Zhang; Jinliang Ji; Yuanyuan Lei; Fujian Qin; Yitong Tao; Ning Li; Jinlei Bian; Zhiyu Li; Maode Lai; Zhixia Qiu (Pharmacological Research)
Inhibiting de novo lipogenesis (DNL) in hepatocytes is a promising strategy for treating metabolic fatty liver diseases. ACLY, a key enzyme in the DNL pathway, has become a therapeutic target for non-alcoholic fatty liver disease (NAFLD). However, its inhibition shows mixed outcomes, depending on interventions and diets. Evidence suggests ACLY inhibition activates the ACSS2-mediated acetate metabolism and the subsequent DNL, though potential mechanisms and possible consequences remain unclear. This study found that targeting hepatic ACLY with AAV8-shRNA failed to improve NAFLD in mice fed a high-fat, high-fructose diet. Instead, it worsened inflammation and liver injury. ACLY inhibition conditionally upregulated DNL enzymes, but consistently activated the ACSS2-acetyl-CoA pathway and suppressed fatty acid oxidation. Further, ACLY inhibition led to polyunsaturated fatty acid accumulation, triggering mitochondrial dysfunction. The resulting ROS redirected carbon flux into acetate, activating the ACSS2-acetyl-CoA pathway, which promoted lipid biosynthesis and exacerbated mitochondrial dysfunction—a vicious cycle that fueled inflammation and liver damage. Dual inhibition of ACLY and ACSS2 broke this cycle by reducing hepatic acetyl-CoA flux, suppressing DNL, enhancing fatty acid oxidation via PPAR-α activation, and improving mitochondrial function. This combined targeting strategy reduced lipid accumulation, alleviated inflammation, and normalized aminotransferase levels, effectively reversing NAFLD progression.